Моноклональные антитела для одностадийного получения высокоочищенной урокиназы - Кратасюк, Г.А.; Якубов, Л.З.; Синицын, В.В.; Домогатский, С.П.; Рохлин, О.В.; Кольцова, С.В.; Быняева, Н.А.; Федорова, З.Д.; Самсонов, Г.В. (Биополимеры и клетка, 1989)
С помощью специально разработанной схемы скрининга получены высокоаффинные и специфичные моноклональные антитела к человеческой урокиназе. На их основе создан иммуносорбент для одностадийного выделения очищенной урокиназы из мочи. За допомогою спеціально розробленої схеми скринінгу отримано високоафінні і специфічні моноклональні антитіла до урокінази людини. На їхній основі створено імуносорбент для одностадійного виділення очищеної урокінази з сечі. Five independent hybridom clones producing monoclonal antibodies with high affinity and specificity for human urokinase are isolated using specially adopted screening technique. Both inhibiting urokinase activity and noninhibiting antibodies are obtained. They do not crossreact with other serin proteases and some of them have dissociation constants lower than 10 pmol/1. Immunosorbents with these monoclonal antibodies are effective for isolation of urokinase from urine: 2 mg of antibodies attached to 1 ml of sepharose binds 0.5 mg of urokinase.